Analysis of Benign Retroperitoneal Schwannomas: A Single-center Experience - Tang, Maosheng; Liu, Wenqing; Chen, Xiaobing; Zou, Boyuan; Liu, Shibo; Xiao, Mengmeng; Luo, Chenghua (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Retroperitoneal schwannomas are rare. The purpose of this study was to present our experience with the diagnosis and treatment of 67 such tumors.Methods We retrospectively analyzed 67 patients with retroperitoneal schwannoma admitted to the Peking University International Hospital from 2015 to 2021.Results Thirty-seven of the 67 patients had no obvious clinical symptoms. Complete excision was obtained in 62 and subtotal excision in 5 cases. In7 cases, tumor resection was combined with organ resection. The intraoperative blood loss was 300 ml (20–9,000 ml), the maximum size of the tumor was 9 cm (2.5–26 cm), and postoperative complication occurred in six cases (9.0%). Compared with abdominal retroperitoneal tumors, pelvic retroperitoneal tumors had larger tumor volume, more bleeding, higher proportion of block resection, and longer postoperative hospitalization time (p < 0.05). The residual mass progressed slowly in five patients with subtotal resection, and no obvious malignant transformation occurred.Conclusion Complete resection of a retroperitoneal schwannoma can achieve a good long-term prognosis. Residual tumor after surgery progresses slowly and rarely become malignant. We recommend early resection after the discovery of a pelvic retroperitoneal schwannoma.
Keywords: schwannoma; retroperitoneal neoplasms; postoperative complications